Evaluating the Effects of 24-Week Intervention with High-Concentration Hydrogen-Rich Water on Body Composition, Blood Lipid Profiles and Inflammation Biomarkers in Individuals with Metabolic Syndrome - Tyler W. LeBaron; Ram B. Singh; Ghizal Fatima; Kumar Kartikey; Jai P. Sharma; Sergej M. Ostojic; Anna Gvozdjakova; Branislav Kura; Mami Noda; Viliam Mojto; et al. (New Horizons in Medicine and Medical Research Vol. 9, 2022)
The objective of this study is to determine the effects of HRW on blood lipids, inflammation, oxidative stress, and glucose levels, as well as phenotypic changes including body mass, and waist-to-hip ratio. Molecular hydrogen (H2) may attenuate oxidative stress, improve cellular function, and reduce chronic inflammation. Pre-clinical and clinical studies have shown promising effects of H2-rich water (HRW) on specific features of metabolic syndrome, yet the effects of long-term, high-concentration HRW in this prevalent condition remain poorly addressed. We conducted a randomized, double-blinded, placebo-controlled trial in 60 men and women with metabolic syndrome. An initial one-week observation period has been used to collect baseline clinical data, followed by a 24-week randomization to either placebo or high-concentration HRW (> 5.5 millimoles of H2 per day). Supplementation with high-concentration HRW significantly reduced blood cholesterol and glucose levels, attenuated serum hemoglobin A1c, and improved biomarkers of inflammation and redox homeostasis as compared to placebo (P < 0.05). In addition, H2 tended to cause a slight reduction in BMI and waist-to-hip ratio. Our findings support the idea that high-concentration HRW could be an effective treatment technique for reducing metabolic syndrome risk factors.